Association of waiting and consultation time with patient satisfaction: Secondary-data analysis of a national survey in Peruvian ambulatory care facilities - Alarcon Ruiz, Christoper A. (2019)
Background: Research suggested that waiting time and consultation time are associated with overall patient satisfaction concerning health services. However, there is a lack of information regarding this subject in Latin American countries, where particular aspects of health systems and population characteristics could modify this association. Our aim was to evaluate the association of waiting time and consultation time with patient satisfaction, in Peruvian ambulatory care facilities and propose a cut-off points of waiting and consultation time based on patient satisfaction. Methods: Cross-sectional secondary data analysis of the National Survey on User Satisfaction of Health Services (ENSUSALUD-2015), a national-wide survey with a probabilistic sample of 181 Peruvian ambulatory care facilities. Patient satisfaction, waiting time, consultation time, and sociodemographic variables were collected from the ENSUSALUD-2015. All variables were collected by survey directly to patients, from the selected ambulatory care facilities, after their consultation. Complex survey sampling was considered for data analysis. In the association analysis, we grouped the waiting time and consultation time variables, every 10 min, because for it is more relevant and helpful in the statistical and practical interpretation of the results, instead of the every-minute unit. Results: The survey was performed in 13,360 participants. Response rate were 99.8 to 100% in the main variables. Waiting time (for every 10 min) was inversely associated with patient satisfaction (aOR: 0.98, 95% CI: 0.97-0.99), although the aOR was lower among those who reported a waiting time ≤ 90 min (aOR: 0.92, 95% CI: 0.89-0.96). Consultation time (for every 10 min) was directly associated with patient satisfaction (aOR: 1.59, 95% CI: 1.26-2.01), although the aOR was higher among those who reported a consultation time ≤ 15 min (aOR: 2.31, 95% CI: 1.66-3.21).